Does online anonymity undermine the sense of personal responsibility?. (May 2019) - Jordan, Tim
This article begins by exploring the media visibility of anonymity online, in particular in relation to trolls and online bullying. It then explores anonymity in the case of Chelsea Manning who leaked US military secrets but only lost anonymity sometime after her leak was made public. This discussion explores issues of responsibility and the reasons for being anonymous. The article then briefly discusses anonymity based on the discussion of the Manning case in relation to the Snowden case, where Snowden refused anonymity, and the Pentagon Papers. The article concludes by pointing out that issues of responsibility in relation to anonymity remain similar whether digital or not, but that anonymity now exists in a context in which there is greater ability to share information between many more people, faster and with radically lowered costs of publishing than before.